A Pathway for The Deficiencies and Challenges of Cervical Cancer Screening In Pakistan - Hanna Khair Tunio; Aftab Ahmed (Liaquat National Journal of Primary Care)
In Pakistan, Cervical cancer is a significant public health challenge. It has become the second most common cancer among women in their reproductive age. In cancer-related deaths, it has emerged as a leading cause of death. Regardless of the availability of tools for screening that are effective and within the approach of the general population, Pakistan still faces issues in the implementation of effective programs for Cervical cancer screening. There is an immediate need for the improvement of awareness regarding cervical cancer screening, its accessibility to the target population, and the provision of the infrastructure to support the screening program in healthcare settings. One of the key barriers to the implementation of an effective program for cervical cancer screening is the lack of widespread awareness among the general population in Pakistan. Studies conducted on cervical cancer screening awareness in Pakistan have shown that women in rural areas are unaware of cervical cancer morbidity and mortality. Their knowledge about its early management through screening is also minimal. According to a study conducted on Human Papillomavirus (HPV) vaccination coverage and public awareness in Pakistan showed that 70% of females are unfamiliar with cervical cancer terminology. They lack understanding of the importance of pap smears. There are insufficient health campaigns and their focus mostly lacks the marginalized population, where it is foremost important to aware females about early screening for the timely diagnosis of the disease [1]. Other barriers that also need the attention of the policymakers are unequal access to the screening services with more privileges to the females belonging to the urban settings than small towns and rural areas [2]. The affordability of screening services which hinders women in low-income families from accessing the screening is also a challenge to the cervical cancer screening program. Those females who are tested and have abnormal results further face challenges for proper follow-up treatment plans and lack of clarity about vaccination against HPV and its role in prevention against HPV types 16 and 18. There is a challenge of cultural barriers which also plays a significant role in the uptake of screening against cervical cancer. Taboos related to the causes of cervical cancer especially in young females and their reproductive health issues hinder the need to take preventive care within females belonging to the conservative communities [3]. Pakistan can improve its screening program against cervical cancer through rigorous work on the deficiencies that need the attention of Policymakers and their role in developing a robust program for the prevention of cervical cancer [4]. This may include integrating cervical cancer screening into routine healthcare services. This further needs a basic approach to first educate the females about cervical cancer, its risk factors like smoking and oral contraceptives, along with the early diagnosis. It is also important to run campaigns about how the early diagnosis of the disease can improve the health of females. Focusing on the dynamics of the rural areas of Pakistan it is important to create awareness and provision of screening services at the doorstep through mobile health clinics and satellite healthcare centers. This will provide a long-term solution for the accessibility issues in rural parts of the country [5]. Cervical cancer screening is a potential tool for the recognition of saving the lives of females in Pakistan. The efforts to address this issue have remained insufficient in Pakistan. The situation can be improved by creating a large population awareness especially targeting the underprivileged population, expanding the services to the communities to reduce accessibility issues, and developing policies to utilize follow-up treatment plan guidelines. Addressing these deficiencies calls for concerted work from policymakers, healthcare professionals, and the general population to affirm that every female has an approach to the preemptive care a female needs for her health.